REVENUE ADMINISTRATION BAITTUL WATTAMWIL MAAL (BMT) PROGRAM APPLICATION EMPHASIS ON - Bambang Ponco Putranto; Susi Wagiyati, S.Kom., MM (Jurnal Sistem Informasi, 1998)
Computerized system within a private or public institutions is very visible role at all for efficient and effective work processes. Provides ease of search and discovery of data and more reliable than the manual method.